Genital infections in high-risk human papillomavirus positive Paraguayan women aged 30-64 with and without cervical lesions. - Alanis Arévalos; Adriana Valenzuela; Pamela Mongelós; Hernán Barrios; María Isabel Rodríguez; Romina Báez; Claudia Centurión; Jaime Vester; Ana Soilán; Marina Ortega; Lorena Meza; Malvina Páez; et al. (PLoS ONE)
Objective To determine the prevalence of genital infections (GIs), including sexual transmitted STIs: Neisseria gonorrhoeae, Chlamydia trachomatis, Mycoplasma genitalium, Trichomonas vaginalis, and opportunistic pathogens that generally do not cause STIs, non-classic STI: Ureaplasma urealyticum, Ureaplasma parvum and Mycoplasma hominis, in women with high-risk oncogenic human papillomavirus (hr-HPV) infection and their association with cervical lesions. Methods A cross-sectional study was carried out including 231 hr-HPV positive women. Of these, 46 has histologically confirmed cervical intraepithelial neoplasia 3 (CIN3) or more (including CIN3 and cervical cancer lesions-CIN3+). GIs were detected by multiplex real time PCR. Odds ratios (OR) were estimated to explore possible associations between GIs and the presence or absence of CIN3+ lesions. Additionally, we examined associations between sociodemographic, sexual, and clinical characteristics and the presence of GIs. Results In total, there were 174/231 cases of GIs corresponding to an overall prevalence of 75.3% (95%CI: 69.4-80.4), being non-classic STIs the most common (72.3%) compared to STIs (12.6%). The most prevalent non-classic STI and STI were U. parvum (49.8%) and C. trachomatis (7.4%), respectively. The odds of presenting GIs were 3 times higher in women under 46 years compared to older counterparts (OR: 3.32, 95%CI: 1.74-6.16), and in women with a normal Pap smear with inflammation compared to those without inflammation (OR: 3.31, 95%CI: 1.15-9.77). GIs were equally present in women with and without CIN3+ lesions. Conclusion We observed an association of GIs with inflammation in the Pap smear, but no association with CIN3+, as some of them are very common and likely part of the normal vaginal flora, suggesting that such infections do not appear to be cofactors in cervical carcinogenesis, although larger prospective studies are needed.